(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to analyze the influence of product innovation and export performance in SME furniture industry in Jepara regency, Indonesia. This research uses a quantitative research approach. The population was 307 SME furniture industries in Jepara. Data collection consists of two types, namely primary data and secondary data. The primary data was a questionnaire submitted by 174 respondents. Secondary data was obtained from BPS Jepara Regency and Jepara Regency Industry and Trade Office, in the form of Jepara Furniture SME (structural equation models) export volume in 2012-2016 and Jepara furniture exporters’ data in 2016. Data analysis techniques are descriptive statistics in which the respondents’ profiles are presented in terms of frequency and percentage and inferential statistics. Descriptive statistics of the research variables was presented in the form of mean, theoretical and actual ranges, mean, and standard deviation. Meanwhile, interval data are presented in the form of mean and standard deviation. The result shows that product innovation and export performance as variables affects significantly to SME furniture industry in Jepara. The results showed that indicator involved in product design has the highest loading factor of 0,803. It has the highest contribution in product design to form innovation product variable following market trend. The highest indicator for export performance is profit growth factor loading of 0.837. This indicator contributes the most in shaping the export performance variable.